Sea Power in South-East Asia - Szumowski, Adrian Rafał (Rethinking Asia in World Politics, 2023)
At the beginning of the 21st Century, South-East Asia is gradually becoming one of the major hubs for international tensions and conflict on a global scale. With surge of People Republic of China capabilities connected with Soft and Hard Power, and re-igniting interest of remaining global players, this region is witnessing adaptation of new strategies and tools not only for war, but also for political and economic expansion. The main aim of this paper is to examine development of tools and strategies associated with sea power, which were developed to manage and exploit during standoff and potential conflict in the region. New quality of international environment is introducing change and evolution to the classical concept associated with classical understanding of sea power – how it is produced, measured, and exploited in contemporary situation. Main hypothesis of this paper will state, that with surge in cost and sophistication of sea power platforms, the primary users are devising new avenues to project their influence in disputed areas of South-East Asia. However, its final usefulness still needs to be tested in real-space entanglements. The paper will be subdivided on four separate parts. First will be devoted to original concepts of Sea Power, according to its founders, such as Alfred Thayer Mahan, Julian Corbett and John Fisher, whose created foundations of what is contemporary known as a Sea Power. Second will embrace the specifics of South-East Asia as a particular region for deployment of Sea Power. It will investigate its political, economic, social, and cultural landscapes ant their ties to Sea Power. Third will investigate the potential change in the nature, strategies and tools associated with Sea Power. And fourth part will encompass possible scenarios for Sea Power implementation in the South-East Asia conflict zone.